2021
DOI: 10.3389/fphar.2021.678685
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Anti-Inflammatory and Antibacterial Effects of QingXiaoWuWei Decoction Based on Network Pharmacology, Molecular Docking and In Vitro Experiments

Abstract: Background and Aim: QingXiaoWuWei Decoction (QXWWD) is a traditional Chinese medicine that is commonly used in clinical settings to treat inflammatory and bacterial diseases. However, there is still a lot to learn about its molecular mechanism. A network pharmacology approach was applied to investigate the pharmacological mechanisms of QXWWD in inflammation treatment.Methods: The basic mechanisms involved in the anti-inflammatory and antibacterial potentials of QXWWD were identified using network pharmacology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…The dietl-eth_ T. garckeana was evaluated for its in vivo anti-inflammatory effects in mice using a xylene-induced ear edema test [ 45 , 46 ]. Healthy mice were divided into five ( n = 5) groups and administered orally with saline, dietl-eth_ T. garckeana (150 and 300 mg/kg BW), or 200 mg/kg aspirin for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…The dietl-eth_ T. garckeana was evaluated for its in vivo anti-inflammatory effects in mice using a xylene-induced ear edema test [ 45 , 46 ]. Healthy mice were divided into five ( n = 5) groups and administered orally with saline, dietl-eth_ T. garckeana (150 and 300 mg/kg BW), or 200 mg/kg aspirin for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the ethanolic extract of the Euphorbia kansui root containing ingenane diterpenoids (euphorkans A and B), together with 16 known analogues, exerted an anti-inflammatory activity that was consistent with Q by inhibiting the effects of certain inflammation mediators, such as TNF-α and IL-6, in a concentration-dependent manner through the inhibition of NF-κB activity [33]. Moreover, the ethanolic extract of the QingX-iaoWuWei decoction, containing quercetin and other ingredients, exhibited synergistic anti-inflammatory activity in the LPS-induced RAW264.7 cell culture via JUN, MAPK1 and AKT1 targets and the mitogen-activated protein kinases (MAPK)/phosphatidylinositol-3 kinase (PI3K)/Akt serine/threonine kinases pathways [34].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study was found in the LPS stimulated Rat-1 fibroblast that luteolin inhibited the linkage between the NF-κB p65 and transcriptional coactivator and suppressed the NF-κB transcriptional activity [ 37 ]. Another study has also found a flavonoid compound quercetin inhibits LPS activated inflammatory responses in mononuclear cells by inhibiting the NF-κB signaling pathways [ 38 ].…”
Section: Discussionmentioning
confidence: 99%